TECHNOLOGICAL ASPECTS IN ESTHETIC CERAMIC BRIDGES - Diana Diaconu-Popa; Anca Vitalariu; Monica Tatarciuc (Romanian Society of Oral Rehabilitation, 2017)
The evolution of fixed prosthodontics through continuous and explosive development of the materials and technologies has exceeded the expectations of many specialists, clinicians and researchers. In the last years it provides to practitioners a huge number of possibilities and methods for morphological and functional dental rehabilitation. For a long time metal ceramic restorations were considered the optimal therapeutic solution due to their special properties (biocompatibility, mechanical resistance, chemical and dimensional stability). The emergence of new materials with superior aesthetic characteristics did changed the therapeutic strategies, and patients‟s aesthetic demands have greatly increased; therefore, we cannot speak today of a functional rehabilitation without a physiognomic recovery as close to perfection. Zirconia materials and pressed ceramic are now two treatment options preferred by patients and practitioners.Our paper aims to present the possibility of functional restoration rehabilitation with pressed ceramic bridges, highlighting the particularities of this method and the importance of the technological factor in getting a prosthetic construction that ensures an optimum oral rehabilitation.Choosing the best material in order to achieve fixed prosthesis is still a subject of controversy, even for specialists, and more studies are necessary to improve the properties of materials and current technologies